COMPARATIVE EFFECTS OF NITROGEN-BASED AND NON-NITROGEN-BASED SUBSTRATES ON THE PROXIMATE CONTENTS OF Pleurotus SPECIES - C. A. Anukwuorji; N. V. Omumu; N. C. Ikegbunam (The Bioscientist)
Pleurotus species are edible mushrooms valued for their nutritional and medicinal properties. This study investigated the comparative effects of nitrogen-based substrates and non-nitrogen-based substrates on the nutritional profile of Pleurotus spp. The substrates used include saw dust, dried banana leaves, rice bran and cowpea husk. Mushroom yield was determined by dividing the total weight of the fruiting bodies from all the flushes by the dry weight of the substrate. The fruiting yield and biological efficiency results showed significantly higher yields (35.6%) and bio-efficiencies (42.1%) in nitrogen-based substrates compared to non-nitrogen-based substrates. Cowpea husk produced the highest yield (195.9 ± 66.0g) and bio-efficiency (65.20 ± 25.3g). Proximate analysis revealed varying nutritional profiles across substrates, with cowpea husk exhibiting higher protein (18.20 ± 7.01%), ash (4.88 ± 2.36%), and crude fiber (5.16 ± 1.90%) content. Rice bran showed higher fat (2.98 ± 0.30%) and carbohydrate (6.290 ± 1.78%) content. Nitrogen-based substrates exhibited superior nutritional profiles than non-nitrogen-based substrates. These findings suggest that nitrogen-based substrates provide essential nutrients for optimal growth and nutritional enhancement of Pleurotus species. It also highlights the importance of substrate selection in optimizing nutritional quality and yield of Pleurotus spp. Nitrogen-based substrates, particularly cowpea husk, are recommended for commercial mushroom production due to their enhanced nutritional profiles and higher yields